Sleep Quality And Type 2 Diabetes (The Review of Diabetic Studies, 2025)
Objectives: Sleep disturbances are prevalent in people with type 2 diabetes (T2DM). The aim of this study is to determine the prevalence of poor sleep quality among patients with T2DM and investigate associated factors.Methods: This is an analytical cross-sectional design which recruited 400 patients with T2DM randomly in, Saudi Arabia. The sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI). Data were collected through face-to-face interviews and reviewing participants’ medical records. Logistic regression analysis was used to identify predictors of poor sleep quality in patients with T2DM.Results: The total PSQI mean score was 7.11±3.53. The results demonstrated that about two-thirds of the patients with T2DM (64.5%) had poor sleep quality. Several factors were significantly associated with poor sleep quality, including old age (p=0.001), married (p<0.001), long duration of diabetes(p<0.001), daily coffee consumption(p<0.001), and presence of depression and anxiety symptoms (p<0.001). Also, the results revealed a significant positive correlation between poor sleep quality and hemoglobin (HbA1c) (p<0.001). HbA1c was a significant independent predictor of poor sleep quality after adjustment for age, marital status, duration of diabetes, coffee consumption, and depression, anxiety, and stress symptoms.Conclusions: Poor sleep quality is prevalent in patients with T2DM in this Saudi. Therefore, healthcare providers should routinely identify and address sleep problems in patients with T2DM to prevent the negative impact of poor sleep quality.